"Semi-real" simulation in the tactical trainings - Kuliev, R. (International Journal of Computer Science in Sport, 2002)
Development of society and sports has made it necessary for all sportsmen to quickly adapt to new training ideas and digest new tactical skills. Now this has been made easier with special tactical training methods.